A comperhensive review: Antimicrobial Resistance in Indonesia One Health Challenge - Ranto Bayu Damanik; Alfiana Laili Dwi Agustin; Agus Widodo; Eka Pramyrtha Hestianah; Danti Nur Indiastuti; Ratna Damayanti; Kuncoro Puguh Santoso; Boedi Setiawan; Rahmi Sugihartuti; Vivi Oktaviana; Rury Mega Wahyuni; Lita Rakhma Yustinasari (VITEK : Bidang Kedokteran Hewan, 2026)
Antimicrobial resistance has become a major global health concern affecting humans, animals, and the environment. The increasing occurrence of antibiotic resistant bacteria threatens the effectiveness of antimicrobial therapy and poses serious public health risks. This review aims to describe the occurrence and distribution of antimicrobial resistant Escherichia coli across humans, animals, wildlife, and environmental sources using a One Health perspective. A literature review approach was conducted by collecting scientific articles published between 2015 and 2025 from international and national databases including PubMed, Scopus, and Google Scholar. Articles were selected based on relevance to antimicrobial resistance in Escherichia coli within human, animal, and environmental contexts. The reviewed studies indicate that Escherichia coli isolates frequently show resistance to commonly used antibiotics such as ampicillin, tetracycline, fluoroquinolones, and third generation cephalosporins. Multidrug resistant strains and extended spectrum beta lactamase producing bacteria have been reported in clinical samples, livestock, companion animals, wildlife, and environmental samples including wastewater and river water. These findings highlight the interconnected nature of antimicrobial resistance transmission between humans, animals, and the environment. Integrated surveillance and responsible antibiotic use are essential to control the spread of antimicrobial resistance through the One Health approach